IMPLEMENTASI MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATA PELAJARAN IPS SEBAGAI UPAYA PENGEMBANGAN KOMPETENSI ABAD KE-21 DI SMP NEGERI 2 PAMANUKAN - Siti Sangadah Indah; Indah Kristina Wulandari; Eneng Serli; Dinna Daniati; Ratna Wulan Munggarani; Tia Ihsantiani; Eneng Martini (LPPM Universitas Cipta Mandiri, 2025)
This study aims to describe the implementation of contextual learning model (Contextual Teaching and Learning/CTL) in Social Sciences (IPS) learning as an effort to develop 21st century competencies at SMP Negeri 2 Pamanukan. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, documentation, and literature studies. The results of the study indicate that the application of CTL syntax which includes constructivism, inquiry, asking, learning communities, modeling, reflection, and authentic assessment, significantly encourages the development of 6C skills (critical thinking, creativity, collaboration, communication, citizenship, and connectivity) in students. This learning strategy makes the learning process more meaningful and contextual, and encourages active participation of students in building knowledge based on real experiences. Despite obstacles such as time constraints and the dominance of conventional methods, CTL has proven effective in supporting learning transformation that is in line with the Independent Curriculum and the demands of the global era.